SANKSI PIDANA KEMATIAN BAGI ORANG KORUPSI DI INDONESIA (Death Criminal Sanctions For Personnel Of Corruption In Indonesia) - Irvino Rangkuti, Alvi Syahrin, Suhaidi, Mahmud Mulyadi (Res Nullius Law Journal, 2021)
The application of capital punishment itself has been regulated in Indonesia as contained in the law. Article 2 paragraph (2) of Corruption Act concerning Eradication of Corruption Crimes. According to Romli Atmasasmita, it was argued that the death penalty for corruptors was effectively implemented in the People's Republic of China (PRC), and it was quite successful to reduce corruption. This certainly can be used as an example in Indonesia in imposing capital punishment for corruptors. The imposition of capital punishment for perpetrators of corruption is urgently needed as "shock therapy" because psychologically the death penalty aims for the benefit of general prevention so that others do not participate in committing crimes. Also, the application of capital punishment is based on the reason that capital punishment is more certain than the prison sentence because the prison sentence is often followed by running away, forgiveness, or because of the release. When compared from an economic standpoint, basically the death sentence is more efficient when compared to life imprisonment. As for the problems that can be formulated, namely: legal arrangements regarding corruption in the Corruption Act; the application of capital punishment sanctions against perpetrators of corruption in Indonesia. The results of the study show that: Corruption is a type of extraordinary crime ("extra-ordinary crime") that must be handled extraordinarily, so that the act is contrary to the 1945 Constitution, therefore it does not need to be protected by the 1945 Constitution. accommodated in Article 2 paragraph (2) of the Corruption Act, must meet the requirements "in certain circumstances" by the Elucidation of Article 2 paragraph (2), but its application has never been implemented, so it is necessary to review the rules "in certain circumstances".